(untitled) (Research, Society and Development, 2022)
Objectives: To investigate the hospital morbidity related to leishmaniasis in a state of Southern Brazil and to analyse the management of the financial resources regarding hospital expenses. Methods: This is a cross-sectional study. The cases of hospital admissions due to leishmaniasis recorded in the state of Paraná between 2008-2018 were obtained by consulting the IT Department of the Unified Health System (DATASUS), Brazil. The profile of the hospitalized patients, the character of medical care and expenses with hospital service were investigated. The data were statistically analysed on Epi Info™ version 3.5.4. Results: The study recorded 3,927 confirmed cases and 61 hospital admissions caused by cutaneous leishmaniasis (31.77%), 42 mucocutaneous (21.88%), 18 visceral (9.37%) and 71 unspecified clinical form (36.98%). Most patients were male (79.17%, 152), of white race (68.75%, 132) and older than 30 (81.77%, 157). The higher number of hospital admissions was due to urgency service (85.41%, 164). The total amount spent on hospitalizations varied in these ten years, with a minimum value of US1,205.43 and a maximum of US5,073.94. Joinpoint regression program 4.6.0. was used for the trend analysis. Conclusions: The expenditures with tertiary care for the treatment of patients with leishmaniasis reflect the need to strengthen basic health care. We believe that the development of health education activities with the population to prevent the leishmaniasis transmission reduces the number of new cases, while the early diagnosis of the disease can avoid medical complications and consequently decrease the costs of hospitalizations.